Emenda Constitucional nº 103/2019 e a Dignidade da Pessoa Humana: o impacto negativo nos benefícios de risco - Renata Raule Machado (2024)
His work intends to make considerations about the latest pension reform, which occurred through Constitutional Amendment No. 103/19, emphasizing the great negative impact on the new rules for calculating risk benefits, namely retirement due to permanent disability and death pension. and the violation of human dignity. To this end, we will provide a brief history of Social Security in Brazil, focusing on the Social Security Regimes. Also, how Mato Grosso do Sul's own Social Security Regime was created, especially given the peculiarity of the State's division. The hypothetical-deductive method was applied in two stages: identifying the formation of values and cultural aspect that tolerates contradictory interests between the individual/insured/beneficiary and the State. For the research, historical and current national legislation was used, obtained from the plateau website platform and in compiled books. The theoretical focus will be evaluative with an emphasis on socio-criticism, as the analysis of the apparent contradiction of values between the objectives of protecting human rights and guaranteeing a fruitful social security must be carried out in compliance with the historical formation of social security, its objectives and its effects on society. Of the changes promoted by the aforementioned Amendment, the worst impact occurred on the values of risk benefits, namely, death pensions and retirements due to permanent incapacity, a time when people are more vulnerable and need values to face their needs. expenses. The aforementioned Amendment was published and, 04 (four) months later, we were surprised by the Covid-19 pandemic, where we had 705,775 deaths. Families, in addition to the loss of their loved ones, were left without money to cover their current expenses, given the abysmal decrease between the amount received as retirement or pension for the deceased and the amount received as a death pension. Since Social Security is a constitutionally guaranteed social right, in addition to being a guarantee provided for in the Universal Declaration of Human Rights, does the aforementioned Amendment violate the dignity of the human person?